Operating room ventilation systems: recovery degree, cleanliness recovery rate and air change effectiveness in an ultra-clean area. (April 2022) - Lans, J.L.A.; Mathijssen, N.M.C.; Bode, A.; van den Dobbelsteen, J.J.; van der Elst, M.; Luscuere, P.G.
Summary: Background: Entrainment test methods are described in most European standards and guidelines to determine the protected area for ultra-clean ventilation (UCV) systems. New UCV systems, such as temperature-controlled airflow (TcAF) and controlled dilution ventilation (cDV) systems, claim the whole operating room (OR) to be ultra-clean. However, current test standards were not developed to assess ventilation effectiveness outside the standard protected area. Aim: To assess and compare the ventilation effectiveness of four types of OR ventilation systems in the ultra-clean area using a uniform test grid. Methods: Ventilation effectiveness of four ventilation systems was evaluated for three different ultra-clean (protected) areas: the standard protected area (A); the area outside the standard protected area (B); and a large protected area (AB). Ventilation effectiveness was assessed using recovery degree (RD), cleanliness recovery rate (CRR) and air change effectiveness (ACE). Findings: RD, CRR and ACE were significantly higher for the unidirectional air flow (UDAF) system compared with the other systems in area A. In area B, the UDAF and cDV systems were comparable for RD and CRR, and the UDAF and conventional ventilation (CV) systems were comparable for ACE. In area AB, the UDAF and cDV systems were comparable for CRR and ACE, but significant differences were found in RD. Conclusion: In area A, the ventilation effectiveness of the UDAF system outperformed other ventilation systems. In area B, the cDV system was best, followed by the UDAF, TcAF and CV systems. In area AB, the UDAF system was best, followed by the cDV, TcAF and CV systems.